Detecting Boosting Weak Signal via A Meminductive Multistable Chaotic System - Kang, Baolin; Qin, Wenjie (Frontiers in Physics, 2022)
In this paper, we rebuild a new meminductive chaotic circuit model based on a Wien-bridge oscillator. Due to the extreme multistability of the meminductive system, it can produce the phenomenon of many infinitely coexisting attractors. Systems that spontaneously produce coexisting oscillations are relatively rare in the study of meminductive circuit systems and are well suited as pseudo-random number generators (PRNG). In this study, a new weak signal detection model is established based on the proposed meminductive system. This detection model can detect boosting weak signals with different amplitudes. The trajectory of objects can be predicted effectively by the boosting line spectrum in the frequency domain. The experimental result shows the feasibility through which the meminductive multistable system is applied in the detection field.